Analisis Faktor – Faktor Yang Mempengaruhi Struktur Modal Dengan Inflasi Sebagai Variabel Moderasi - Adelyne Teng, Jonnardi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research was to analyze the influence of Profitability, Liquidity, and Firm Size on Capital Structure with Inflation as a moderating variable. The sample used in this study is manufacturing company that listed on the Indonesia Stock Exchange (IDX) 2013-2017. The result of this research shows that Profitability has no significant effect and negative on Capital Structure. Liquidity has significant effect and negative on Capital Structure and Firm Size has no significant effect and positive on Capital Structure. There is inflation as a moderating variable that strengthens up the relation between Firm size and Capital Structure.